Changes in free-roaming dog population demographics and health associated with a catch-neuter-vaccinate-release program in Jamshedpur, India - Lauren Margaret Smith; Tamara Kartal; Sanjay Rawat; Amit Chaudhari; Ashok Kumar; Rajesh Kumar Pandey; Rupert Julian Quinnell; Lisa M. Collins (PLoS ONE, 2025)
India’s large free-roaming dog populations contribute to significant human health, environmental, and social challenges. Population management strategies, such as catch-neuter-vaccinate-release (CNVR), aim to reduce dog numbers, improve their welfare, and reduce human-animal conflict. Humane Society International (HSI; now operating as Humane World for Animals), in partnership with the Animal Health Foundation, implemented a CNVR program in Jamshedpur, neutering and vaccinating over 20,000 dogs. This study evaluated the impact of this program on dog health, population structure and size. The study areas encompassed 10 sites within Jamshedpur, including both intervention sites where CNVR was directly applied and sites without direct intervention. Data was collected from May 2014 until December 2018, including bi-annual street surveys, as well as clinical data from the dogs captured and treated. We fit logistic regression, negative binomial, and binomial mixed effects models to assess changes in dog population characteristics, health, and reproductive conditions over time in relation to the CNVR intervention. We found that, over the period of this study, the probability of dogs entering the clinic with mange, transmissible venereal tumours, and pregnant significantly reduced. Street surveys showed an increase in sterilised dogs, with higher proportions observed in CNVR-treated sites, although the counts of dogs observed increased overall. The age-structure of free-roaming dogs remained stable over time. In CNVR-treated areas, the probability of observing lactating female dogs decreased, whereas it increased in untreated sites. This work contributes to the growing body of knowledge investigating the impact of dog population management interventions. Continued monitoring and evaluation of CNVR programs are required to identify optimal coverage required to reduce population size effectively.